A Convex Hull‐Based New Metric for Quantification of Bladder Wall Irregularity in Pediatric Patients With Congenital Anomalies of the Kidney and Urinary Tract. (12th June 2017) - Stember, Joseph N.; Newhouse, Jeffrey; Behr, Gerald; Alam, Shumyle
Abstract : Objectives: Early identification and quantification of bladder damage in pediatric patients with congenital anomalies of the kidney and urinary tract (CAKUT) is crucial to guiding effective treatment and may affect the eventual clinical outcome, including progression of renal disease. We have developed a novel approach based on the convex hull to calculate bladder wall trabecularity in pediatric patients with CAKUT. The objective of this study was to test whether our approach can accurately predict bladder wall irregularity. Methods: Twenty pediatric patients, half with renal compromise and CAKUT and half with normal renal function, were evaluated. We applied the convex hull approach to calculate T, a metric proposed to reflect the degree of trabeculation/bladder wall irregularity, in this set of patients. Results: The average T value was roughly 3 times higher for diseased than healthy patients (0.14 [95% confidence interval, 0.10–0.17] versus 0.05 [95% confidence interval, 0.03–0.07] for normal bladders). This disparity was statistically significant ( P < .01). Conclusions: We have demonstrated that a convex hull‐based procedure can measure bladder wall irregularity. Because bladder damage is a reversible precursor to irreversible renal parenchymal damage, applying such a measure to at‐risk pediatric patients can help guide prompt interventions to avert disease progression.